The Effect of Rise Time in Dynamic Stress Intensity Factor for Impact Loading - Mohammad Damghani Nouri; حسین رحمانی (مجله مدل سازی در مهندسی, 2015)
Dynamic stress intensity factor determination on crack tip under impact loading is widely investigated. The history of impact loading in analytical researches is considered to be step function but experimental tests show that in impact loading, a small time is needed to the loading rise from zero to ultimate amount. This interval time is called rise time. In this research, Firstly, Dynamic stress intensity factor for a semi- infinite crack on a plate under impact loading is determined analytically but the history of loading is considered as a ramp function. Then a comparison between the analytical solution in this paper and the last results and also with finite element is done. Finally, the experimental method for changing the rise time on impact loading is presented and the effect of it in dynamic stress intensity factor is researched.